Quantitative approach to track lipase producing Pseudomonas sp. S1 in nonsterilized solid state fermentation. (12th March 2014) - Sahoo, R.K.; Subudhi, E.; Kumar, M.
<x xml:space="preserve">Abstract</x> Proliferation of the inoculated Pseudomonas sp. S1 is quantitatively evaluated using ERIC–PCR during the production of lipase in nonsterile solid state fermentation an approach to reduce the cost of enzyme production. Under nonsterile solid state fermentation with olive oil cake, Pseudomonas sp. S1 produced 57·9 IU g−1 of lipase. DNA fingerprints of unknown bacterial isolates obtained on Bushnell Haas agar (BHA) + tributyrin exactly matched with that of Pseudomonas sp. S1. Using PCR‐based enumeration, population of Pseudomonas sp. S1 was proliferated from 7·6 × 104 CFU g−1 after 24 h to 4·6 × 108 CFU g−1 after 96 h, which tallied with the maximum lipase activity as compared to control. Under submerged fermentation (SmF), Pseudomonas sp. S1 produced maximum lipase (49 IU ml−1) using olive oil as substrate, while lipase production was 9·754 IU ml−1 when Pseudomonas sp. S1 was grown on tributyrin. Optimum pH and temperature of the crude lipase was 7·0 and 50°C. Crude enzyme activity was 71·2% stable at 50°C for 360 min. Pseudomonas sp. S1 lipase was also stable in methanol showing 91·6% activity in the presence of 15% methanol, whereas 75·5 and 51·1% of activity were retained in the presence of 20 and 30% methanol, respectively. Thus, lipase produced by Pseudomonas sp. S1 is suitable for the production of biodiesel as well as treatment of oily waste water. Significance and Impact of Study This study presents the first report on the production of thermophilic organic solvent tolerant lipase using agro‐industry waste in nonsterile solid state fermentation. Positive correlation between survival of Pseudomonas sp. S1 and lipase production under nonsterile solid state fermentation was established, which may emphasize the need to combine molecular tools and solid state fermentation in future studies. Our study brings new insights into the lipase production in cost‐effective manner, which is an industrially relevant approach